A plant design on the production of propylene glycol from crude glycerol - Arlantico, May Antonette P.; Briones, Rowena M.; Dy, Trixie Ruth N.; Tanyag, Bryan Merk E.
The report gives an economical assessment of a renewable route towards propylene glycol (PG). Propylene glycol or 1, 2-propanediol is a clear, colorless, viscous, practically odorless and tasteless liquid. PGs multifunctional structure allows it to be used in a wide variety of applications such as antifreeze agents, unsaturated polyester resins, personal care products, cosmetics, paints and coatings, food products and plasticizers.The preferred route, towards propylene glycol is through hydrogenolysis of crude glycerol from biodiesel industry in vapor-phase packed bed reactor using copper chromite as catalyst. The process was first introduced by a team led by Dr. Galen Suppes from University of Missouri Columbia. It has the advantage of processing crude glycerol at moderate conditions with high selectivity towards propylene glycol and with little selectivity towards ethylene glycol and other by-products confirmed and the rest are yet to be identified.Crude glycerol and hydrogen will be sourced from local companies while copper chromite catalyst will be imported. The viability of this design project largely depends on crude glycerol prices and propylene prices. The present situation wherein price of crude glycerol continues to fall and propylene glycol price continues to increase suggests that will project is a feasible undertaking.The plant is designed to meet the Philippine annual demand, as well as make ample supply for exporting. It is to produce 11,000 tons of PG at full capacity but is planned to operate only at 50% of its full capacity on its first 5 years.The estimated return on equity at 50% operation is 22%, and the plant is expected to recover its capital investment after 4 years and 6 months with a selling price of Php 125.00 per kg propylene glycol which is less than the current local market prices.